Pemanfaatan Video Pembelajaran Terhadap Kemampuan Kognitif Anak Usia 4-5 Tahun - Sri Wahyuningsi Laiya; Nunung S. Jamin; Rosanti Bilotango (Student Journal of Early Childhood Education, 2023)
The study's subject involved 10 children aged 4-5 years and applied qualitative method. The research findings indicated that using learning videos effectively stimulates cognitive development in 4-5-year-old children at TK Damhil UNG Kindergarten. Children's cognitive ability in number recognition is stimulated through a video that introduces numbers 1 to 10. The video helps children remember and store the information in their brains, thus enhancing their intelligence. In terms of color recognition ability, the provided video interprets various colors associated with objects familiar to children, such as plants, fruits, and animals. This helps children understand colors correctly, sharpen their visualization skills, and improve their ability to accurately differentiate and identify different colors. In terms of listening skills, children's abilities are stimulated through a video story about Indonesia, which includes the shape and colors of the Indonesian flag, the national emblem, and the names of presidents. This video stimulates children's thinking, emotions, and motivation to process information, thus enhancing their listening skills. In terms of auditory skills, the provided video contains sounds of various animals.